PENGARUH DOSIS PUPUK KANDANG SAPI DAN ZA TERHADAP PERTUMBUHAN BIBIT CACAO (THEOBROMA CACAO L.) - I Dewa Made Duada (AGRICA, 2014)
Both organic and inorganic fertilization determines the growth of the cocoa seed. The correct dose of cow manure and ZA (as a source of N) can improve the growth of the cocoa seed. This pot test was conducted in farmer land in Banjar of Selanbawak Kaja Agriculture Department, Selanbawak Village, Marga Sub district, Tabanan Regency, ± 250 m dpl, starting from February 2010 until May 2010. The goal of this test is to investigate the impact of cow manure and ZA dose on the growth of the cocoa seed. A complete random block design was implemented in this test with two treatment factors, namely cow manure dose (0, 300, 600, and 900 g seed-1) and ZA dose (0,0; 1,0; 2,0; and 3,0 g seed-1). All treatments were repeated three times. The result of the test shows that interaction between cow manure and ZA doshas real impact on the growth of the cocoa seed. The dose of 900 g cow manure seed-1with 2,0 g dose of ZA seed-1contributes the highest weight of fresh seed (each of 9,79 and 3,12 g seed-1) and oven-dry weight (each of 12,69 and 4,47 seed-1) both at the age of 75 and 90 hsbd. 3,0 dose of ZA seed-1 in the similar cow manure dose (900 g seed-1) did not provide any real differences to fresh seed and dry oven weight of seed. 900 g dose of cow manure seed-1 with 2,0 g dose of ZA seed-1also provides the highest and the widest numbers of leaves at the second ages, and the highest of stem diameter at the age of 90 hsbd. The optimum dose of cow manure and ZA was not gained yet in this test. There was a linear relationship between cow manure dose and ZA dose with fresh seed weight and dry oven weighting 90 hsbd. The dose of 900 g cow manure seed-1and 2,0 g ZA seed-1can be used to obtain the best cocoa seed growth until the age of 90 hsbd. Further study is required by using the dose combination of both fertilizer to investigate the growth of seed after the age of 90 hsbd.